2016
DOI: 10.1101/gr.204479.116
|View full text |Cite
|
Sign up to set email alerts
|

Specific down-regulation of spermatogenesis genes targeted by 22G RNAs in hybrid sterile males associated with an X-Chromosome introgression

Abstract: Hybrid incompatibility (HI) prevents gene flow between species, thus lying at the heart of speciation genetics. One of the most common HIs is male sterility. Two superficially contradictory observations exist for hybrid male sterility. First, an introgression on the X Chromosome is more likely to produce male sterility than on autosome (so-called large-X theory); second, spermatogenesis genes are enriched on the autosomes but depleted on the X Chromosome (demasculinization of X Chromosome). Analysis of gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 74 publications
1
44
1
Order By: Relevance
“…These observations suggest that the process of X inactivation in male meiosis would be especially sensitive to disruption in hybrids (“fragile male” hypothesis; Wu & Davis, ), potentially leading to hybrid male sterility. The limited available data are consistent with this idea, based on X‐linked introgression lines between C. briggsae and C. nigoni that implicates chromatin misregulation via small RNA pathways (Li et al., ).…”
Section: Exceptionalismmentioning
confidence: 79%
See 1 more Smart Citation
“…These observations suggest that the process of X inactivation in male meiosis would be especially sensitive to disruption in hybrids (“fragile male” hypothesis; Wu & Davis, ), potentially leading to hybrid male sterility. The limited available data are consistent with this idea, based on X‐linked introgression lines between C. briggsae and C. nigoni that implicates chromatin misregulation via small RNA pathways (Li et al., ).…”
Section: Exceptionalismmentioning
confidence: 79%
“…However, these experiments with homozygous introgressions of C. briggsae DNA inserted into a C. nigoni genomic background demonstrated that the X‐chromosome is associated with all of the male‐specific hybrid dysfunction in terms of fertility and viability (Bi et al., ). Spermatogenesis, in particular, is perturbed by these X‐linked introgressions and leads to incompatibility mediated by misregulation of small RNAs (Li et al., ). The biogenesis of this particular class of small RNA, known as 22G RNAs, involves post‐transcriptional processing of coding sequences with subsequent targeting and modulation of chromatin in conjunction with the CSR‐1 and other argonaute proteins (Claycomb, ).…”
Section: Molecular Evolution and The Large‐x Effectmentioning
confidence: 99%
“…Notably, the introgression spans the entire region of the second piRNA cluster on the C. briggsae Chromosome IV [45,46], which raises the possibility that incompatibility of these piRNAs between C. briggsae and C. nigoni that is responsible for the hybrid F1 inviability caused by crossing in both directions. Consistent with this notion is another piRNA cluster unique to C. briggsae on the Chromosome I [46]. The homozygosity of the region covering this cluster led to inviability in the hybrid F1 male and female progeny regardless of the parent of origin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Small RNAs perform multiple functions that are fundamental to genome stability, from gene expression regulation to heterochromatin assembly and dosage compensation – many of which have been reported as “broken down” in hybrids (previous section and [61]). The diverse functions of small RNAs have been extensively reviewed elsewhere [e.g.…”
Section: Mechanism 6: Small Rnas and Transposable Elementsmentioning
confidence: 99%